The Oath Keepers : patriotism and the edge of violence in a right-wing antigovernment group - Jackson, Sam (Professor of social sciences) (Columbia University Press, 2020)
"In the past decade, America has seen the wild growth of the militia movement. After remaining stable during George W. Bush's presidency, the number of patriot/militia groups climbed from 149 in 2008 to 512 in 2009 before peaking at 1,360 in 2012. During this time, its supporters have engaged in protests, interfered with government action (with the Bundy Ranch standoff and the Malheur Refuge occupation), plotted acts of terrorism (for example, with a Kansas plot to bomb an apartment complex home to many Somali refugees), and carried out violence against law enforcement and civilians. Among the most visible and vocal of these organizations is the Oath Keepers. Formed in 2009, the Oath Keepers quickly became perhaps the most prominent group in the American anti-government patriot/militia movement, gaining notoriety for their involvement in the Bundy Ranch standoff of 2014 and the Malheur Refuge occupation of 2016. Along with the rest of the patriot/militia movement, the Oath Keepers has grown dramatically since 2009, and today the group claims some 30,000 members. They give voice to a recurrent form of American politics: anger and distrust of the government combined with a valorization of violence. Despite growing media coverage, the Oath Keepers and groups like it have received very little attention from researchers. Through a case study of the Oath Keepers and a textual analysis of the group's publications (an archive of over one million words), Jackson explores how the group uses core American political values and American history to interpret the political context it finds itself in, to provide examples for appropriate forms of political behavior given that context, and to gain support from more Americans"--